Children's endowment, schooling, and work in Ethiopia - Seife Dendir (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
I investigate the relationship between children's endowment and parental investment using a rich dataset on a cohort of children from Ethiopia, who were surveyed at ages eight, twelve and fifteen. Children's endowment is measured by scores on tests of cognitive skills/ability. A child's enrollment in school, participation in work and work hours are employed as measures of parental investment in human capital. The results provide strong evidence of reinforcing parental investment - higher ability children are more likely to be enrolled in school and less likely to work and, conditional on participation, also work fewer hours. These results are mostly robust to addressing potential feedback effects between schooling and test scores, especially for the latter ages, and household heterogeneities. On the policy front, the results suggest that the seeds of inequality in human capital and earnings capability during adulthood may be sown quite early in childhood, and thereby underscore the importance of interventions that, among others, attempt to improve prenatal and early life health and nutrition, which are often cited as the sources of deficiencies in children's cognitive ability.
Keywords: D10; I24; O12; J13; 330; endowment; human capital; schooling; child work/labour; Ethiopia